Residual red cells in blood components: A multisite study of fully automated enumeration using a hematology analyzer. Issue 2 (17th November 2020) - Cavagnetto, Chloe; Alejo Blanco, Richard; McKenna, Hollie; Willmott, Laura; Aydogdu, Elif; Akinyemi, Nicola; Standring, Helena; Procter, Simon; Lagerberg, Johan W.; Johansson, Elin; Croxon, Harry; de Korte, Dirk; et al.
Abstract: Background: Manufacture of platelet concentrates (PCs) and plasma may fail to remove all residual red blood cells (rRBCs). Measuring rRBCs for compliance to guidelines has proven challenging, leading to an absence of a consensus methodology. Sysmex hematology analyzers with the Blood Bank mode (BB mode) analysis option offer the potential for automated rRBC counting. We therefore performed a two‐site appraisal of the system. Study Design and Methods: Performance characteristics were determined using platelet and plasma samples spiked with RBCs. Sample stability (n = 47) and the impact of sample type were also assessed. Components (platelets, n = 1474; plasma, n = 77) prepared using different routine manufacturing methods were tested to assess variation in rRBC concentration. Results: Linearity studies up to 19 000 RBCs/μL demonstrated good correlation between expected and observed results (R 2 ≥ 0.9731), and flow cytometric results also correlated well with BB mode (R 2 = 0.9400). Precision analysis gave a limit of quantitation of 6 to 7 RBCs/μL, and carryover was 0.03%. Ethylenediaminetetraacetic acid and plain tube results were not significantly different ( P ≥ 0.10), and samples were stable up to 24 hours. Apheresis PCs produced at two sites had lower rRBC concentrations (medians, 17 and 13 RBCs/μL) than those produced with the buffy coat method either manually (median, 681 RBCs/μL) or with the automated Terumo Automated Centrifuge and Separator Integration process (median, 81 RBCs/μL). All PCs failing visual inspection as having RBCs ≥4000 RBCs/μL were also detected by the BB mode. Conclusion: The BB mode had acceptable performance characteristics and has the potential for integration into a fully automated process control system for rRBC enumeration in plasma and PCs.